Lymphocyte Activation Gene 3 (Lag3) Contributes to α-Synucleinopathy in α-Synuclein Transgenic Mice - Gu, Hao; Yang, Xiuli; Mao, Xiaobo; Xu, Enquan; Qi, Chen; Wang, Haibo; Brahmachari, Saurav; York, Bethany; Sriparna, Manjari; Li, Amanda; Chang, Michael; Patel, Pavan; et al. (Frontiers in Cellular Neuroscience, 2021)
Aggregation of misfolded α-synuclein (α-syn) is the major component of Lewy bodies and neurites in Parkinson’s disease (PD) and related α-synucleinopathies. Some α-syn mutations (e.g., A53T) in familial PD recapitulate the α-syn pathology in transgenic mice, which supports the importance of pathologic α-syn in driving the pathogenesis of α-synucleinopathies. Lymphocyte activation gene 3 (Lag3) is a receptor of α-syn fibrils facilitating pathologic α-syn spread; however, the role of Lag3 in mediating the pathogenesis in α-syn transgenic mice is not clear. Here, we report that depletion of Lag3 in human α-syn A53T transgenic (hA53T) mice significantly reduces the level of detergent-insoluble α-syn aggregates and phosphorylated ser129 α-syn, and inhibits activation of microglia and astrocytes. The absence of Lag3 significantly delays disease progression and reduces the behavioral deficits in hA53T transgenic mice leading to prolonged survival. Taken together, these results show that Lag3 contributes to the pathogenesis in the α-syn A53T transgenic mouse model.